THE DRAMATIC STRUCTURE OF TOURISM ADVERTISEMENT “WONDERFUL INDONESIA EPISODE TORAJA-MAKASSAR” - Afrianto, Damar Tri; Santiko, Putut Bayu (Seni Media Rekam ISI Surakarta, 2020)
The study of digital advertisement of the tourism was based on the potential of dramatic elements seen in the